Effect of Water Alternating Gas (WAG-N2 ) after Water or Gas Flooding on Crude Oil Recovery in Sandstone Reservoirs - Alagorni, Abubaker H.; Zulkefli, Yaacob; Nour, A. H.; Radzuan, Junin (IOP Publishing, 2019)
Previous studies showed that nitrogen injection could recover oil up to 45-90 % of the Original Oil in Place (OOIP) of the reservoir. Additionally, when applying Water Alternating Gas (WAG-N2), recovery can be improved by combining gas and water and having better gas mobility control by reducing viscous fingering and density tonging, as well as contacting the un-swept zones, leading to an improved microscopic displacement. The objective of this study is to determine the total Oil Recovery Factor (ORF) of WAG-N2 process either after Water Flooding (WF) or after Gas Flooding (GF) in sandstone reservoirs. The results showed that with the following conditions: 38.8° API gravity oil, injection rate of 0.6cm3/m, injection pressure of 2000 psi (1378.59 kpa), WAG rate of 1:1, and Sand pack temperature of 70°C, the maximum ultimate ORF was 71.2 % in WAG after WF and 52.42 % of WAG after GF. On the other hand, WF provided ORF of 65.6 % when compared with GF recovery (29.03 %).